Assessment of Peguero Lo-Presti Criteria for Electrocardiographic Diagnosis of LVH in Indian Subjects - Patted, Suresh V; Porwal, Sanjay C; Ambar, Sameer S; Prasad, M R; Chincholi, Akshay S; Hesarur, Vishwanath; Patil, Vaibhav (Cardiology and Cardiovascular Medicine, 2018)
Background and objectives: The sensitivity of ECG to diagnose LVH (Left ventricular hypertrophy) is low. Peguero Lo-Presti have proposed new ECG criteria for LVH to improve the sensitivity of ECG while maintaining the high specificity when compared to older well-established criterion like Cornell voltage and Sokolow Lyon. The objective of this study was to evaluate Peguero Lo-Presti criteria in the diagnosis of LVH in patients with hypertension. Methodology: 400 consecutive patients with hypertension who have visited the cardiology OPD (Out Patient Department) and have undergone ECG and 2D echocardiography were included in the study. Patients with valvular regurgitation (Grade II or higher), myocardial infarction, valvular stenosis, LV dysfunction, pericardial disease, COPD (Chronic obstructive pulmonary disease), bundle branch blocks, atrial fibrillation or flutter were excluded from the study. Results: LVH was diagnosed in 192 (48%) of the patients by 2D echocardiography. Of the 192 patients, 104 patients had LVH based on Peguero Lo-Presti criteria with a sensitivity of 54.17%. Cornell Voltage criteria was positive in 76 out of 192 patients with a sensitivity of 39.58% and Sokolow-Lyon criteria was positive in 56 out of 192 with a sensitivity of 29.17%. The Peguero Lo-Presti ECG criteria had a higher sensitivity (54.17%) and specificity (91.35%) in the diagnosis of LVH by ECG. Conclusion: Peguero Lo-Presti criteria to diagnose LVH has higher sensitivity and specificity compared to Sokolow-Lyon and Cornell voltage criteria.